Synthesis and reactivity of an osmium(iii) aminoguanidine complex. Issue 30 (8th July 2019) - Xiang, Jing; Su, Qian-Qian; Luo, Li-Juan; Lau, Tai-Chu
Abstract : An osmium(iii ) aminoguanidine complex (OsGNH2 ) has been synthesized, which possesses rich redox chemistry. Abstract : The biological activities of aminoguanidine (GNH2 ) and its derivatives have been extensively studied due to their properties as radical scavengers and antioxidants. Some of their biological activities may result from their binding to various metals present in biological systems. However, the reactivity of coordinated aminoguanidines has not been investigated. We report herein the synthesis, structure and reactivity of a novel osmium(iii ) complex bearing the parent aminoguanidine, mer -[OsNHC(NH2 )(NHNH2 )(L )(CN)3 ] − (OsGNH2, HL = 2-(2-hydroxyphenyl)benzoxazole). The antioxidant properties ofOsGNH2 have been investigated by reactions with various oxidants, including O2, H2 O2, m -chloroperbenzoic acid ( m -CPBA) and Ce(iv ). Various osmium products are produced, which depend on the type of oxidant used.OsGNH2 is readily oxidized by O2 or H2 O2 under ambient conditions to afford an osmium(iii ) formamidine complex, [Os III (NH2 C{NH)(L )(CN)3 ] − (OsFA, FA = formamidine). With m -CPBA, the nitrosyl complex, mer -[Os(NO)(L )(CN)3 ] − (OsNO ), is formed instead. On the other hand, the nitrido complex mer -[Os(N)(L )(CN)3 ] − (OsN ) is produced when the one-electron oxidant (NH4 )2 [Ce IV (NO3 )6 ] (Ce(iv )) is employed. The molecular structures ofOsGNH2 andOsFA have been determined by X-ray crystallography. The oxidation ofOsGNH2 toOsFA by O2 or H2 O2 is proposed to go through initial dehydrogenation to give a diazoamidine intermediate. In the oxidation by m -CPBA and Ce(iv ), it is proposed that the initially formedOsFA is further oxidized toOsNO andOsN, respectively, via osmium(iii ) hydrogen cyanamido and osmium(iv ) cyanoimido intermediates.